A scientometric review of global research on technology in physical education - Daharis; Gazali, Novri; Perdima, Feby Elra; Abdullah, Khairul Hafezad; Rahmadani, Ahmad (UIR Press, 2023)
Since COVID-19, technology-based physical education has been normal and is emerging. This paper is intended to identify the development of scientific publications and map educational technology research pertinent to physical education. The keywords